Modelagem hidrológica e das perdas de solo: suas relações com as formas de relevo e uso do solo na bacia do rio Taperoá - PB - Silva, Marcela Alves da (2015)
The modelling of river basins is becoming an essential tool for management of water resources, mainly in the basins located in semi-arid portion, such as Taperoá River basin. This basin drains an area of 5,667 km², and has been suffering with the variability of hydrological processes in the semi-arid portion of Paraiba. The objective of this study is to analyze the relationship between forms of land use and cover and the runoff and erosion processes in the Taperoá River basin. In order to development of the study, rainfall, temperature and humidity data from 1970 to 1993, soil types map, land cover map and digital elevation model with spatial resolution of 30 m were used. The model was calibrated and validated by comparing simulated mean monthly runoff with observed long-term mean monthly runoff for runoff gauge Poço das Pedras. The results showed the effectiveness of the model for the analysis of runoff process with average observed runoff = 6.86 m³/s and average simulated runoff = 7.73 m³/s, while the sediment yield was 2.5 t/ha/yr. From the morphometric data and maps generated it can be performed further studies in the areas of preservation and probable land use, facilitating the process of planning and management of water resources.